Observation of significant differences between electromagnetic and acoustic emissions during fracture processes: A study on rocks under compression loading - Clavijo Ramírez, Jorge Enrique; Wang, H; Sanchez, S (IOP Publishing Ltd, 2019)
Electromagnetic radiation (known as electromagnetic emissions) related to processes of loading and fracture in different types of materials (from metals to rocks) has been widely reported. The physical mechanisms behind these emissions are still under discussion, however, it is commonly accepted that they are created by some of the micro-cracks that appear in the sample during fracture processes. Nucleation and growing of micro-cracks generate mechanical waves (acoustic emissions), therefore, each electromagnetic emission should be linked with some acoustic event. Furthermore, it is expected that the electromagnetic and acoustic activities (number of emissions per second) have the same general characteristics. Contrary to what is usually reported, we find that there are significant differences between acoustic and electromagnetic emissions in loading processes on rocks. These differences were detected during the compression of a typical laboratory-scale sample of granite when it is compressed at a rate of around 20 kPa/s. We found two important discrepancies: i) There were at least 20 electromagnetic bursts (out of around 200) that were not coincident with any acoustic event. ii) The electromagnetic activity in general shows its maximum value when acoustic activity is very low. Both emissions just coincide at the moment of the final collapse. These results strongly suggest the existence of a non-fracture mechanism related to the origin of electromagnetic emissions. This could have important consequences for the field of non-destructive assessment of materials and even in the study of earthquake precursors and forecasting.

La radiación electromagnética (conocida como emisiones electromagnéticas) relacionada con los procesos de carga y fractura en diferentes tipos de materiales (desde metales hasta rocas) ha sido ampliamente reportada. Los mecanismos físicos que subyacen a estas emisiones siguen siendo objeto de debate, pero se acepta comúnmente que son creadas por algunas de las microgrietas que aparecen en la muestra durante los procesos de fractura. La nucleación y el crecimiento de las microfisuras generan ondas mecánicas (emisiones acústicas), por lo que cada emisión electromagnética debería estar relacionada con algún evento acústico. Además, se espera que las actividades electromagnéticas y acústicas (número de emisiones por segundo) tengan las mismas características generales. Contrariamente a lo que se suele informar, encontramos que existen diferencias significativas entre las emisiones acústicas y electromagnéticas en los procesos de carga de rocas. Estas diferencias se detectaron durante la compresión de una muestra típica de granito a escala de laboratorio cuando se comprime a una velocidad de unos 20 kPa/s. Encontramos dos discrepancias importantes: i) Hubo al menos 20 explosiones electromagnéticas (de unas 200) que no coincidieron con ningún evento acústico. ii) La actividad electromagnética en general muestra su valor máximo cuando la actividad acústica es muy baja. Ambas emisiones coinciden justo en el momento del colapso final. Estos resultados sugieren fuertemente la existencia de un mecanismo de no-fractura relacionado con el origen de las emisiones electromagnéticas. Esto podría tener importantes consecuencias en el campo de la evaluación no destructiva de materiales e incluso en el estudio de precursores y predicción de terremotos.